Dry Sliding wear of AA2219/Gr Metal matrix composites. (2018) - Saravanakumar, A.; Sivalingam, S.; kumar, L. Rajesh
Abstract: Composites are the materials that can be combined together to obtain many advantageous properties, on which studies and experiments are carried out on their synthesis, structure, characterization, properties and performance. Aluminium alloy composites are currently under research widely for its variety of properties and availability. 2-series aluminium alloys have copper as the second highest constituent and so they have good corrosion and wear properties. Graphite, due its self-lubricating property, is the most widely used element in automobile and aerospace industries where wear resistance plays a major role. In the present work aluminium Alloy AA2219 is used as matrix material and graphite is used as reinforcement. Composites are manufactured by stir casting and were tested for their wear behaviourDesign of experiment is done by taguchi method L27 orthogonal array and regression equation was obtained using ANOVA. Analysis shows that load is the most influencing factor followed by speed and percentage graphite. Regression equation was obtained based on the parameters and responses. The R 2 value was found to be 91% and so the prediction capability of the equation is good. Wear tracks were characterized by Scanning Electron Microscopy (SEM) to study the influence of reinforcement on the wear behaviour and the images reflected the influence of graphite on the wear tracks.